Cannabis: a multifaceted plant with endless potentials - Fordjour, Eric; Manful, Charles F.; Sey, Albert A.; Javed, Rabia; Pham, Thu Huong; Thomas, Raymond; Cheema, Mumtaz (Frontiers in Pharmacology, 2023)
Cannabis sativa, also known as "hemp" or "weed," is a versatile plant with various uses in medicine, agriculture, food, and cosmetics. This review attempts to evaluate the available literature on the ecology, chemical composition, phytochemistry, pharmacology, traditional uses, industrial uses, and toxicology of Cannabis sativa. So far, 566 chemical compounds have been isolated from Cannabis, including 125 cannabinoids and 198 non-cannabinoids. The psychoactive and physiologically active part of the plant is a cannabinoid, mostly found in the flowers, but also present in smaller amounts in the leaves, stems, and seeds. Of all phytochemicals, terpenes form the largest composition in the plant. Pharmacological evidence reveals that the plants contain cannabinoids which exhibit potential as antioxidants, antibacterial agents, anticancer agents, and anti-inflammatory agents. Furthermore, the compounds in the plants have reported applications in the food and cosmetic industries. Significantly, Cannabis cultivation has a minimal negative impact on the environment in terms of cultivation. Most of the studies focused on the chemical make-up, phytochemistry, and pharmacological effects, but not much is known about the toxic effects. Overall, the Cannabis plant has enormous potential for biological and industrial uses, as well as traditional and other medicinal uses. However, further research is necessary to fully understand and explore the uses and beneficial properties of Cannabis sativa.